Gibberellin Signaling in Barley Aleurone Cells. Control of SLN1 and GAMYB Expression - Gubler, Frank (American Society of Plant Physiologists, 2002)
We have previously identified GAMYB, a gibberellin (GA)-regulated transcriptional activator of α-amylase gene expression, in aleurone cells of barley (Hordeum vulgare). To examine the regulation of GAMYB expression, we describe the use of nuclear run-on experiments to show that GA causes a 2-fold increase in the rate of GAMYB transcription and that the effect of GA can be blocked by abscisic acid (ABA). To identify GA-signaling components that regulate GAMYB expression, we examined the role of SLN1, a negative regulator of GA signaling in barley. SLN1, which is the product of the Sln1 (Slender1) locus, is necessary for repression of GAMYB in barley aleurone cells. The activity of SLN1 in aleurone cells is regulated posttranslationally. SLN1 protein levels decline rapidly in response to GA before any increase in GAMYB levels. Green fluorescent protein-SLN1 fusion protein was targeted to the nucleus of aleurone protoplasts and disappeared in response to GA. Evidence from a dominant dwarf mutant at Sln1, and from the gse1 mutant (that affects GA “sensitivity”), indicates that GA acts by regulating SLN1 degradation and not translation. Mutation of the DELLA region of SLN1 results in increased protein stability in GA-treated layers, indicating that the DELLA region plays an important role in GA-induced degradation of SLN1. Unlike GA, ABA had no effect on SLN1 stability, confirming that ABA acts downstream of SLN1 to block GA signaling.